A simple dynamic climate cooperation model - Robert Schmidt; Eugen Kovac (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
A standard result from the game theoretic literature on international environmental agreements is that coalitions are either `broad but shallow' or `narrow but deep'. Hence, the stable coalition size is small when the potential welfare gains are large. We modify a standard climate coalition game by adding a - seemingly - small but realistic feature: we allow countries to delay climate negotiations until the next `round' if a coalition forms but decides to remain inactive. It turns out that results are surprisingly different under this modification. In particular, a large coalition with deep emissions cuts forms if countries are sufficiently patient. Our results also indicate that countries should try hard to overcome coordination problems in the formation of a coalition. A more cooperative outcome may then be reached, and it may be reached more quickly.
Keywords: D62; F53; Q54; 330